Analysis of the Main Indicators on Romania's Public Debt in the Period 2015-2020 - Ioana LAZARESCU; Viorica IOAN; Andreea DABIJA (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics, 2021)
This article aims to highlight how important it is to analyze and effectively manage a state's public debt in order to maintain a stable macroeconomic situation. In this sense, we made an analysis of the main indicators of public debt. During the period 2015-2020, the level of indebtedness in relation to economic activity decreased, with the exception of 2020, which, under the impact of the Covid-19 pandemic, shows an increase in public debt. A thorough research of the public debt is needed in the the current context of the Covid-19 pandemic. Among the analyzed indicators we can mentione: public debt per capita in lei and in euro, public debt related to GDP and exports of goods and services, government public debt service.